2018
DOI: 10.1016/j.jcf.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Implementing the International Committee on Mental Health in Cystic Fibrosis (ICMH) guidelines: Screening accuracy and referral-treatment pathways

Abstract: Mental health screening is complex, particularly in adolescents. Nonetheless, it is a first valuable step to improve mental health care in CF. The need for psychological support is greater than anticipated by the TIDES study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 21 publications
1
33
0
Order By: Relevance
“…This is not surprising as it was the main tool administered in the TIDES study, but was shown to underestimate depression and anxiety in CF 6 . Indeed, recent work indicates that there is much more psychopathology in people with CF and their parent caregivers than was estimated by the TIDES study 11 . In comparison with formal face-to face psychological assessment, the GAD-7 and PHQ-8/9 were able to identify all those with the most severe psychopathology and all those who endorsed the suicide ideation screening item.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This is not surprising as it was the main tool administered in the TIDES study, but was shown to underestimate depression and anxiety in CF 6 . Indeed, recent work indicates that there is much more psychopathology in people with CF and their parent caregivers than was estimated by the TIDES study 11 . In comparison with formal face-to face psychological assessment, the GAD-7 and PHQ-8/9 were able to identify all those with the most severe psychopathology and all those who endorsed the suicide ideation screening item.…”
Section: Discussionmentioning
confidence: 97%
“…For those reporting less severe difficulties on screening, agreement with formal assessment was less accurate. Typically, this was because people underestimated/underreported their symptoms at screening (with patients and caregivers requiring treatment referrals following psychological assessment) 11 .…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of having a life-limiting chronic condition with a very high treatment and symptom burden result in challenges to well-being and has implications on the mental health of the person and their carers. 18,[137][138][139] Overall, there is a higher prevalence of anxiety and depression in adults with CF, and recent guidelines have indicated the need for mental health and well-being to be discussed openly and frequently with people with CF. 137 A regular screening process using short questionnaires has been instituted in many centers, with a follow-up plan to provide support for those with capital problems.…”
Section: Mental Health and Well-beingmentioning
confidence: 99%
“…137 A regular screening process using short questionnaires has been instituted in many centers, with a follow-up plan to provide support for those with capital problems. 139,140 Many people with CF find the CF team to be the main source of psychological support, but clear criteria for support from clinical psychology and/or psychiatry should be in place. 137 It is very important that mental health and wellbeing is acknowledged by CF MDTs as a key part of delivering CF care and that it is considered at all interactions.…”
Section: Mental Health and Well-beingmentioning
confidence: 99%
“…Patients reported minimizing their responses on the screening forms and expressed concern for negative consequences. Use of formal clinical assessment revealed more accurate reporting of issues and allowed for reports of additional difficulties . Thus, the screening will identify significant mental health concerns, but further assessments may be necessary for less significant difficulties that can still affect care and quality of life (QoL).…”
Section: Patient‐reported Outcomes/prioritiesmentioning
confidence: 99%